2016
DOI: 10.4238/gmr.15038697
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD4 SNPs with fat percentage of Holstein cattle

Abstract: ABSTRACT. Cluster of differentiation 4 gene (CD4) is well known for its role in immunity, but its effects on production traits remain to be elucidated. The present study was designed to explore single nucleotide polymorphisms (SNPs) in the exons, flanking introns, and promoter of CD4, as well as to analyze their effects on milk production traits (percentage of protein, fat, and lactose; mastitis indicator traits somatic cell count; and somatic cell score). A total of 10 SNPs, including eight in the exon and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…This study documents the occurrence of several polymorphisms in the genomic sequence of the entire CD4 gene in a sample of Simmental genomic sires. Many of these polymorphisms, as already reported by other authors (Usman et al, 2016;Zeb et al, 2020), were in perfect linkage disequilibrium in the surveyed 34 genomes. In the present work we investigated the possible effect of genomic variants in CD4 on the deregressed MACE EBV indexes for SCS, an indicator of udder health status and for milk quality and quantity.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This study documents the occurrence of several polymorphisms in the genomic sequence of the entire CD4 gene in a sample of Simmental genomic sires. Many of these polymorphisms, as already reported by other authors (Usman et al, 2016;Zeb et al, 2020), were in perfect linkage disequilibrium in the surveyed 34 genomes. In the present work we investigated the possible effect of genomic variants in CD4 on the deregressed MACE EBV indexes for SCS, an indicator of udder health status and for milk quality and quantity.…”
Section: Discussionsupporting
confidence: 81%
“…The analysis of the genetic variants of the CD4 gene highlights that SNP 11 (rs110955838) is in very close linkage disequilibrium with most of the variants present in the coding and regulatory areas of the gene. This is also evident from the results obtained by other authors in the analysis of the association between some SNPs of CD4 and production traits in dairy cattle (Usman et al, 2016;Zeb et al, 2020). He et al (2011) reported a significant association between the SNP g.13598 C > T of the CD4 gene in intron 6, which corresponds to the SNP 29 (rs110421401) and which is in perfect linkage disequilibrium with the SNP 11, with the production traits of milk and protein yield in Chinese Holsteins, in agreement with our results on Simmental sires.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations